Current management of incidental gallbladder cancer: A review. (February 2022) - Feo, Claudio F.; Ginesu, Giorgio C.; Fancellu, Alessandro; Perra, Teresa; Ninniri, Chiara; Deiana, Giulia; Scanu, Antonio M.; Porcu, Alberto
Abstract: Early-stage gallbladder cancer (GBC) is mostly discovered incidentally by the pathologist after cholecystectomy for a presumed benign disease. It is the most common malignancy of the biliary tract with a variable incidence rate all over the World. The majority of patients with GBC remain asymptomatic for a long time and diagnosis is usually late when the disease is at an advanced stage. Radical surgery consisting in resection of the gallbladder liver bed and regional lymph nodes seems to be the best treatment option for incidental GBC. However, recurrence rates after salvage surgery are still high and the addition of neoadjuvant/adjuvant chemotherapy may improve outcomes. The aim of the present review is to evaluate current literature for advances in management of incidental GBC, with particular focus on staging techniques and surgical options. Highlights: Early-stage gallbladder cancer are is usually diagnosed incidentally after a cholecystectomy for a presumed benign disease. Despite advances in cross-sectional imaging and surgical techniques incidental gallbladder cancer staging may be challenging. Radical liver resection with lymphadenectomy is indicated in most patients with unexpected gallbladder cancer. Major determinant of gallbladder cancer prognosis remains tumor biology rather than extent and type of surgical resection. New minimally invasive techniques for re-resection of incidental gallbladder cancer require more evidence before widespread use.